Pengaruh Penggunaan Media Pembelajaran Quizwhizzer Terhadap Hasil Belajar Peserta Didik pada Pembelajaran IPAS Kelas V SD Negeri 6 Sungai Raya - Maharani, Inneke Alda (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the influence of using the QuizWhizzer instructional media on the learning outcomes of fifth-grade students at Public Elementary School 6 Sungai Raya. The research approach used is a quantitative approach. The research design employed is quasi-experimental research with the Nonequivalent Control Group Design type. The population included in this study consists of all fifth-grade students at Public Elementary School 6 Sungai Raya. The sample in this study comprises the fifth-grade students of class 5A (experimental class) and class 5B (control class) at Public Elementary School 6 Sungai Raya. The technique used for selecting the experimental and control classes is Purposive Sampling. The hypothesis testing used a paired t-test preceded by prerequisite analysis tests, namely the normality test and homogeneity test. The results of the study showed a significant difference in learning outcomes between the experimental class using QuizWhizzer instructional media and the control class using PowerPoint instructional media. The average post-test score of the experimental class was 76.09, better than the average post-test score of the control class, which was 66.37. Based on the hypothesis testing using the paired t-test, it was found that the significance value for the two-sided p was 0.001 < 0.05, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha).